Effect of supplementation of graded levels of oat fodder to mustard straw in crossbred heifers - PANDEY, D N; MALIK, P K; TIWARI, R K (The Indian Journal of Animal Sciences, 2011)
The study was conducted to investigate the effect of different levels of oat fodder supplementation on dry matter intake and nutrient digestibility of mustard straw in crossbred heifers. From the data it can be observed that the graded level of oat fodder supplementation to the mustard straw based diet, can increase DM intake as well as nutrient digestibility in crossbred heifers. Thus, the oat fodder can be useful as a supplementing source to the mustard straw based diet in the ration of ruminants.Â